(untitled) (Education in the 21st Century, 2023)
The article presents the results of a survey of the teachers of physical education. The analysis revealed a number of problems hindering the implementation of physical education in the general 24 education of the Republic of Armenia and the effective teaching of "Physical Culture" school subject The problem. Currently, the negative dynamics of the health status, insufficient level of physical fitness, lack of interest and stable motivation for systematic physical training of schoolage children are observed, from primary to high school. In this case, school physical education, with its main component of “Physical Culture”, is aimed to overcome the abovementioned problems. However, the effective implementation of this process is hampered by a number of issues.